Performance evaluation of a submerged membrane bioreactor for the treatment of brackish oil and natural gas field produced water - Kose, Borte; Ozgun, Hale; Ersahin, Mustafa Evren; Dizge, Nadir; Koseoglu-Imer, Derya Y.; Atay, Burcu; Kaya, Recep (Elsevier Science Bv, 2012)
Produced water, which is co-produced during oil and gas manufacturing, represents one of the largest sources of oily wastewaters. Therefore, treatment of this produced water may improve the economic viability and lead to a new source of water for beneficial use. In this study a submerged hollow fiber membrane bioreactor (MBR) has been studied experimentally for the treatment of brackish oil and natural gas field produced water. This type of wastewater is also characterized with relatively moderate to high amount of salt, oil and total petroleum hydrocarbons (TPH). However, the bacteria which are growing in conventional activated sludge and MBR cannot survive at these strict conditions, therefore acclimation of the bacteria is of vital importance. The performance of the biological system, membrane permeability, the rate and extent of TPH biodegradability have been investigated under different sludge age and F/M ratios. The results obtained by gas chromatography analyses showed that the MBR system could be very effective in the removal of TPH from produced water and a significant improvement in the effluent quality was achieved. (C) 2011 Elsevier By. All rights reserved.
Keywords: High salinity; Membrane fouling; Produced water; Submerged membrane bioreactor; TPH removal